KAJIAN PSIKOANALISIS TOKOH DANANG PADA NOVEL RAHASIA TERGELAP SURGA KARYA BRIAN KHRISNA - Aini, Dewi; Ramadhani, Tazkia Zharifa; Lestari, Wanda Bunga; Halimah, Halimah (HISKI, 2024)
PSYCHOANALYSIS STUDY OF THE CHARACTER DANANG IN THE NOVEL THE DARKEST SECRET OF HEAVEN BY BRIANAbstractThis research aims to analyze the novel